Study of Anaerobic and Aerobic Fertilizers of Organic Waste Treatment - Fadela, Dian Mira; Zakaria, Ahmad; Pradipta, Adya Rizky (Indonesian Journal of Chemical Studies, 2024)
Phosphorus is a critical nutrient for plant growth, significantly enhancing agricultural productivity and ecosystem sustainability. Organic waste-based fertilizers offer a sustainable solution to boost soil phosphorus levels while addressing waste management challenges. This study evaluated the phosphorus content of anaerobic and aerobic fertilizers derived from organic waste, focusing on factors that influence phosphorus dynamics during composting. Composting methods and feedstock composition affected phosphorus transformation and availability, with temperature, moisture, aeration, and microbial activity playing pivotal roles in mineralization, immobilization, and solubilization. The experiment used market waste, pineapple peel, dry leaves, sawdust, water, sugar, manure, and EM4. The composting process involved weekly monitoring of pH, temperature, and compost height. The results showed that the pH of the anaerobic compost ranged from 7.2 to 7.4, meeting the SNI 19-7030-2004 standard. The mature compost color was brownish-black, which also complied with the standard. Phosphorus contents as P2O5 were 1712 mg/kg in aerobic fertilizer and 2653 mg/kg in anaerobic fertilizer. Phosphorus is crucial for root development, water, and nutrient absorption, and enhances plant tolerance to drought. It also affects flower and fruit formation, affecting crop yield quality and quantity. This study highlighted the importance of understanding phosphorus dynamics to optimize nutrient management and improve organic waste utilization in agriculture. Future research should explore the phosphorus transformation mechanisms and innovative composting techniques to enhance phosphorus availability for plant uptake